(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: The study aims to assess the status of diabetes and the related risk factors of people living in Hanoi. Methods: The total study subjects were 1060 people aged 20-74 living in Hanoi. Descriptive, crosssectional study design according to the descriptive study sample size formula. Randomly select two investigation areas. The subjects participating in the study were asked about their disease, examined, and OGTT. Results: The rate of diabetes was 5.7%, with impaired glucose tolerance at 7.4%, and the rate of undiagnosed people was approximately 60%. This study also demonstrated the association between living in urban areas, overweight/obesity, high blood pressure, and diabetes. Conclusion: There is a relationship between the risk factors of overweight/obesity, hypertension, and the risk of diabetes. Living in urban areas has a higher risk of diabetes than in the suburbs.